THE ROLE OF NON-PROFIT ADVERTISING IN THE ORGANIZATION OF PUBLIC RELATIONS OF ORGANIZATIONS OPERATING IN THE SOCIAL SPHERE - V.S.Alekseeva; M.N. Sharustamova (American Journals Publishing, 2022)
This scientific article analyzes the role of non-profit advertising in the organization of public relations of organizations operating in the social sphere, analyzes the practice of its application in social work.
Keywords: social sphere, public, communication, organization, social thought, advertising, social advertising, non-profit advertising, social life, efficiency, quality.